Pengaruh Daya Tarik Wisata Terhadap Minat Berkunjung Kembali Ke Wisata Sajuta Janjang Kabupaten Agam - Firda Aulia Rahmi; Feri Ferdian (Universitas Katolik Widya Karya Malang, 2023)
This research discusses the impact of tourist attractions on interest in returning to the Sajuta Janjang in Agam Regency, which is motivated by a significant decrease in the visits every year number, pre-research which states that as many as 72% of visitors are not interested in visiting again and there are still negative comments on Google review about Sajuta Janjang. The method for research used is a technique of quantitative method with a approach in causal associative and the technique for sampling uses a purposive sampling which is determined at 220 samples. The technique for data collection uses a questionnaire prepared on a Likert scale which has been tested for validity and reliability. The technique for data analysis uses PLS-SEM software. The R square results show that tourist attraction has a big influence on interest in returning to visit with a percentage value of 70.5% while the remaining percentage of 29.5% is influenced by other factors. The test of hypothesis results obtained a t-statistic of 48.1 > 1.96 and a p value of 0.00 < 0.05, so the research results indicate that the tourist attraction variable has a significant effect on interest in returning to visit. In this research, the conclusion that Ha was accepted and Ho was rejected.